On the edge of a tradition: Some prolegomena to paratexts in Malay rental manuscripts. Issue 132 (4th May 2017) - van der Putten, Jan
ABSTRACT: Malay manuscript culture(s) were based around a number of ruling houses and religious centres that were dispersed in the Malay world. The chirographical tradition which was not long-standing swiftly disappeared at the turn of the 20th century as colonialism brought mass education, print literacy and forms of modernity in general. In this final phase of the manuscript culture the printing industry and an ongoing monetisation of economic and cultural transactions characterised the transfer to a modern literary production based on western models and have left their marks in the manuscripts that continued to be produced. This article discusses a few broad changes that have led to the inclusion of new or changed paratexts in manuscripts of this period, namely a heightened sense of manuscript as valuable object, which arguably led to an increase of ownership statements, and a shift in the consumption of the text from orally/aurally to more visually oriented modes of consumption, leading to an increase of illustrations in the manuscripts. Paradoxically perhaps, more orally/aurally oriented, narrative poetic forms ( syair ) constituted the mainstay of the indigenous lithographic book production, but not of the collections of manuscripts produced to be rented out to local readers in urban centres, which form the material for this project. However, syair did feature in these manuscripts, often as a rhymed colophon, to remind the borrower to treat the manuscript with care and respect, and not to forget to pay the fees to its owner whose livelihood depended on them.